Rancangan Alat untuk Efektivitas Pengisian Antiscale di PT. PJB Gresik Berdasarkan Analisis Postur Kerja Menggunakan Metode Rapid Entire Body Assessment - Muhammad Iqbal Ash Shidiq; Deny Andesta; Yanuar Pandu Negoro (Jurnal Serambi Engineering, 2022)
PT PJB is the largest electricity producer on the islands of Java and Bali. Chemicals are needed to expedite the production system and also the durability of the tools used. Antiscale is one that is used in PJB's external water treatment system, namely the Desalination Plant unit. Filling of chemicals into the tank through a manual system carried out by experts. The load is quite heavy and the distance is quite far making workers feel tired quickly. This study aims to determine the working posture conditions on the job of filling antiscale chemicals at PT. PJB UP Gresik. The method used in this study is using the REBA method. The results of data processing and analysis indicate that the working posture conditions in the activity of filling antiscale chemicals into the tank are less ergonomic. The average final score points to 11, which means it has a very high level of risk and action needs to be taken now. Actions that need to be taken to reduce the risk of work accidents are by modifying the line on the Desalination Plant unit so that chemicals can be directly transferred into the tank using a pump. Of course, by considering the aspect of cost and equipment procurement.